Effects of Neuroactive Amino Acids Derivatives on Cardiac and Cerebral Mitochondria and Endothelial functions in Animals Exposed to Stress / T. A. Popova …[et al.] - Popova, T. A.; Prokofiev, I. I.; Mokrousov, I. S.; Perfilova, V. N.; Borisov, A. V.; Lebedeva, S. A.; Dudchenko, G. P.; Tyurenkov, I. N.; Ostrovsky, O. V. (Universiti Teknologi MARA Cawangan Selangor, 2017)
Introduction: To study the effects of glufimet, a new derivative of glutamic acid, and phenibut, a derivative of γ-aminobutyric acid (GABA), on cardiac and cerebral mitochondria and endothelial functions in animals following exposure to stress and inducible nitric oxide synthase (iNOS) inhibition. Methods: Rats suspended by their dorsal cervical skin fold for 24 hours served as the immobilization and pain stress model. Arterial blood pressure was determined using a non-invasive blood pressure monitor. Mitochondrial fraction of heart and brain homogenates were isolated by differential centrifugation and analysed for mitochondrial respiration intensity, lipid peroxidation (LPO) and antioxidant enzyme activity using polarographic method. The concentrations of nitric oxide (NO) terminal metabolites were measured using Griess reagent. Hemostasis indices were evaluated. Platelet aggregation was estimated using modified version of the Born method described by Gabbasov et al., 1989. Results: The present study demonstrated that stress leads to an elevated concentration of NO terminal metabolites and LPO products, decreased activity of antioxidant enzymes, reduced mitochondrial respiratory function, and endothelial dysfunction. Inhibition of iNOS by aminoguanidine had a protective effect. Phenibut and glufimet inhibited a rise in stress-induced nitric oxide production. This resulted in enhanced coupling of substrate peroxidation and ATP synthesis. The reduced LPO processes caused by glufimet and phenibut normalized the endothelial function which was proved by the absence of average daily blood pressure (BP) elevation episodes and a significant increase in platelet aggregation level. Conclusion: Glufimet and phenibut restrict the harmful effects of stress on the heart and brain possibly by modulating iNOS activity.